1996
DOI: 10.1021/la951030w
|View full text |Cite
|
Sign up to set email alerts
|

First Example of Surfactants Enclosing a Semipolar Nitrogen−Boron Bond

Abstract: We describe a new surfactant family whose hydrophilic head contains a semipolar N+−B- bond in a stable aminopropylborane structure. These compounds were synthesized by hydroboration of allylic amines with good yields (>90%). Parameters characterizing their surface activity (critical micelle concentration, surface tension, superficial excess, molecular area at the water−air interface) along with the phase diagram in a water−isooctane−butanol system were determined. The compounds show promise for use in organize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This provides further reaction-based evidence that the BN bond in aminoboranes contains substantial double-bond character . While to our knowledge no multistep syntheses have employed this hetero-ene rearrangement yet, applications of amine-boranes and aminoboranes containing alkenyl substituents have been reported 1 …”
Section: Introductionmentioning
confidence: 64%
“…This provides further reaction-based evidence that the BN bond in aminoboranes contains substantial double-bond character . While to our knowledge no multistep syntheses have employed this hetero-ene rearrangement yet, applications of amine-boranes and aminoboranes containing alkenyl substituents have been reported 1 …”
Section: Introductionmentioning
confidence: 64%
“…They have also examined the interaction of these polymers with semiconducting single-walled carbon nanotubes (SWNTs) using different spectroscopies, and finally examined the ability of these polymer-SWNTs to modulate fluorescence emission in response to different saccharides. Baboulene et al synthesized some amino organo boron amphiphilic molecules that have been shown to have interesting surfactant properties. In recent reports, it was established that long chain amino-boronic acid and its salt shows amphiphilic character in aqueous solution with excellent surface-active properties. , Karpichev and co-workers very recently reported a new approach for creating water-soluble functionalized vesicles employing N -alkyl-3-boronopyridinium triflates (alkyl = CH 3 , C 12 H 25 , C 16 H 33 ) as sensors for monosaccharides .…”
Section: Introductionmentioning
confidence: 99%
“…There are five major groups of surfactants characterized by the charge of their polar moiety as a result of negatively or positively charged or nonionized functional groups: anionic, cationic, nonionic, amphoteric (zwitterionic), and semipolar. …”
Section: Introductionmentioning
confidence: 99%